2023
DOI: 10.1101/2023.02.09.23284763
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Confirmation of theMIR204n.37C>T heterozygous variant as a cause of chorioretinal dystrophy variably associated with iris coloboma, early-onset cataracts and congenital glaucoma

Abstract: Four members of a three-generation family with early-onset chorioretinal dystrophy were shown to be heterozygous carriers of the n.37C>T in MIR204. The identification of this previously reported pathogenic variant confirms the existence of a distinct clinical entity caused by a sequence change in MIR204. The chorioretinal dystrophy was variably associated with iris coloboma, congenital glaucoma, and premature cataracts extending the phenotypic range of the condition. In silico analysis of the n.37C>T var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The pathogenic variant in miR‐204 was first reported in a case of retinal degeneration associated with ocular coloboma, characterized by iris keyhole‐shaped defects, sometimes accompanied by congenital cataract (Conte et al., 2015). In 2023, this pathogenic variant was observed also in a Czech family and associated with congenital glaucoma, besides RP and iris coloboma (Jedlickova et al., 2023). In our patient, WES revealed a miR‐204 n.37C>T variant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathogenic variant in miR‐204 was first reported in a case of retinal degeneration associated with ocular coloboma, characterized by iris keyhole‐shaped defects, sometimes accompanied by congenital cataract (Conte et al., 2015). In 2023, this pathogenic variant was observed also in a Czech family and associated with congenital glaucoma, besides RP and iris coloboma (Jedlickova et al., 2023). In our patient, WES revealed a miR‐204 n.37C>T variant.…”
Section: Discussionmentioning
confidence: 99%
“…(2011) later identified a variant of miR‐184 linked to keratoconus and early‐onset cataracts. MiR‐204 is the first reported miRNA variant with a causal role in inherited retinal dystrophies in two Caucasian families (Conte et al., 2015; Jedlickova et al., 2023). Other miRNAs have been linked to IBD only in mouse models.…”
Section: Discussionmentioning
confidence: 99%
“…While one of these reports documented adult onset cataracts in mice lacking both miR-204 and miR-211 57 , none of these studies reported congenital cataracts or microphthalmia in mice lacking miR-204 expression, suggesting that embryonic lens development in mice does not require miR-204. Interestingly, a dominant point mutation in miR-204 is associated with several ocular disorders including early-onset cataracts in humans 60 . In contrast to the apparent normal embryonic lens development in mice lacking miR-204 , morpholino-induced knockdown of miR-204 in medaka fish disrupted both lens and retina development by interfering with the regulation of Meis2 11 .…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted January 30, 2024. ; https://doi.org/10.1101/2024.01.29.577818 doi: bioRxiv preprint several ocular disorders including early-onset cataracts in humans 60 . In contrast to the apparent normal embryonic lens development in mice lacking miR-204, morpholinoinduced knockdown of miR-204 in medaka fish disrupted both lens and retina development by interfering with the regulation of Meis2 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a dominant point mutation in miR-204 is associated with several ocular disorders, including early-onset cataracts in humans. 68 In contrast to the apparent normal embryonic lens development in mice lacking miR-204, morpholino-induced knockdown of miR-204 in medaka fish disrupted both lens and retina development by interfering with the regulation of Meis2. 14 Surprisingly, deletion of either of the two abundantly expressed miRNAs (miR-1 and miR-184) had no significant effect on the morphologic embryonic development of the mouse lens.…”
Section: Discussionmentioning
confidence: 99%